PENGARUH PENGGUNAAN MODEL THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA MATERI KALOR - Pahlawan, Reza; Siregar, Dedes Asriani (Jurnal Physics Education (PhysEdu), 2020)
Abstract This study aims to know whether there is a significant influence of using Think Pair Share (TPS) learning model on students’ physic achievement on the topic heat at the tenth grade students of SMA Negeri 1 Nagajuang. The research was conducted by using experimental method with 60 students as the sample and they were taken by using total sampling technique. Test and observation were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using TPS learning was 91.06 (very good category) and (b) the average of students’ heat achievement before using TPS learning model was 60 (less category) and after using TPS leaning model was 89.77(very good category). Furthermore, based on inferential statistic by using ttestone tail, the result showed that ttable was less than tobserved (1.91<8.51), it means, there is a significant influence of using TPS learning model on students’ physic achievement on the topic heat at the tenth grade students of SMA Negeri 1 Nagajuang.